Особенности содержания микросреды личности - Иванов, А.В. (My University, 2013)
The purpose of the teacher is to develop the team as an assistant and an advocate for the individual, and the development of a child's ability to defend itself. A look at the child as a subject of its own development poses a different challenge and support, not only as external to his pedagogical action, but also as a kind of specific activity of the child - self-defense.